GJAE is Preparing for Future Developments in the Scientific System: New Policies Regarding Data and AI - Silke Hüttel; Jens Rommel; Ramona Teuber; Martin Banse; Carola Grebitus (German Journal of Agricultural Economics, 2025)
-